Perbandingan Kinerja Reksadana Saham Syariah Dan Reksadana Saham Konvensional - Ansari, Ilham; Pamungkas, Aldi; Z, Qirsa Zahrota; Nadia, Putri; Yunita A, Vera; Aqila, Salfa; Khansa D, Afifah; Salsabila A, Mutiara; Yunitasari, Nita (Jurnal Ilmiah Wahana Pendidikan, 2024)
Apart from the development of the Indonesian capital market, investment funds are also developing. After the development of mutual funds, mutual funds began to implement Islamic sharia principles in their business strategies. This business strategy has an investment policy and this is the main difference that differentiates Islamic mutual funds from conventional ones. This research was conducted with the aim of studying, explaining and analyzing how the performance of sharia mutual funds compares with conventional investment mutual funds, especially investment mutual funds listed on the Stock Exchange. This research includes sharia stock investment mutual funds and conventional stock investments listed on the Indonesia Stock Exchange. The sampling technique in this research was purposive judgment sampling technique. Samples are selected based on sample characteristics with decisive sample selection criteria. The sample used for this research consisted of five conventional stock mutual funds registered on the IDX and five sharia stock investment mutual funds registered on the IDX for the 2020-2022 observation period, consisting of 10 mutual funds. To prove the best performance of stock mutual funds, this research uses a t-test using the observation method and the independent sample t-test method. After carrying out this analysis, it shows that conventional stock mutual funds have better performance than sharia stock mutual funds based on an average risk value that is smaller than sharia stock mutual funds, namely 0.589 > 0.005.